Environmental Energy Sustainability at Universities - Montoya, Francisco G.; Perea Moreno, Alberto Jesús (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The use of renewable energies and energy saving and efficiency are needs of global society and universities. Universities have a large responsibility and social impact, as they are an example and engine of social change. Universities, in the European context, must be at the forefront of ESA processes, seeking to be at the same level as, and preferably higher than, the rest of society, seeking a goal of 20% renewable energy for 2020 and, in the longer term, greater energy efficiency based on a diverse use of renewable energy and studying the feasibility of other energy processes (cogeneration, trigeneration, etc.). The application of renewable energies and energy efficiency allow universities to make significant savings in their costs and contribute to sustainable development and the fight against climate change. Actions in pursuit of these goals in addition to the objective of energy saving should promote research and form an example for the university community. This book aims to advance the contribution of energy saving and the use of renewable energies in order to achieve more sustainable universities.